Policies and practices for teaching sociocultural diversity : report on the survey on initial education of teachers in sociocultural diversity - Arnesen, Anne-Lise.; Birzea, Cezar; Dumont, Bernard; Essomba, Miguel Angel; Furch, Elisabeth; Vallianatos, Angelos; Ferrer, Ferran (Strasbourg : Council of Europe Publishing, 2008)
Although teaching and management of diversity are taken into account in almost all the countries participating in the survey, the "enhanced value" of diversity, which implies the creation of conditions for inclusive participation favorable to equal opportunities for all, is not unanimously approved. This report underlines that teacher education institutions play an important role, in collaboration with policy makers, in drafting study programs, but also in defining national policies concerning teacher education. It is the result of a survey on the initial training of teachers in sociocultural diversity in Europe, carried out in 16 countries within the framework of the project "Policies and practices for teaching sociocultural diversity" launched by the Steering Committee for Education of the Council of Europe in 2006. An analysis of replies from practitioners completes the results of the survey.--Publisher's description.
General introduction -- Sociocultural diversity : content and context -- Summary of the results of the national reports on pre-service teacher training in sociocultural diversity -- Summary of the results of the interviews on pre-service teacher training in sociocultural diversity -- Conclusions and recommendations.
Keywords: interkulturalno obrazovanje; obrazovanje nastavnika